Changes in leptin in relation to increased testosterone levels associated with Eurycoma Longifolia Jack (Tongkat Ali) root extract consumption in male rats - Faisal, Ghasak Ghazi; Haque, Mainul; Najmuldeen, Ghazi Faisal; Mustafa Al-Ahmad, Basma Ezzat; Al-Ani, Ali Sabri Radeef; Alattraqchi, Ahmed Ghazi (Phcog.Net, 2017)
Objectives: Eurycoma longifolia jack root extract has been known for its aphrodisiac and anabolic properties. Our study aimed at investigating the effects of this extract on the serum leptin in relation to the well-known effects on testosterone levels of male rats. Methodology: Twenty-four mature male Albino Wistar rats were used in this study. The rats were divided into 3 groups; control, group A and group B. Body weight was recorded for the rats in all groups. Group A received 5mg/kg twice daily of pure Eurycoma Longifolia root extract. Group B received 10mg/kg twice daily of the same extract. The duration of treatment was 6 weeks at the end of which, serum leptin and testosterone levels were analyzed in all groups and body weight recorded. Results: The mean serum leptin and testosterone levels for the control were 1.13±0.13ng/ml and 0.79±0.07ng/ml respectively. While for group A were1.09±0.19ng/ml, 0.89±0.16ng/ml and for Group B were 0.89±0.16ng/ml,1.75±0.1ng/ml respectively. The rats in the treated groups showed decrease in body weight in comparison to the control which was not significant in group A (p=0.867) and significant in group B (p=0.042). Statistical analysis showed that the serum leptin level of group B was significantly lower than that of control group (p=0.001) and group A (p=0.03). On the other hand, no significant difference in serum leptin levels was observed between the control group and group A. The serum testosterone level was significantly higher in group B than control and group A while group A did not show a statistically significant difference than control. Conclusion: Eurycoma Longifolia root extract can significantly decrease serum leptin levels in relation to the rise in serum testosterone levels. Eurycoma Longifolia consumption also causes a significant decrease in total body weight pointing to the possibility of decreased body fat content.